Spatial Planning Policy in Mitigation of Adverse Impact of Development and Prevention of Natural Disasters - Syarif Hidayatulloh (Jurnal Justiciabelen, 2025)
Good spatial planning policies play a crucial role in mitigating the negative impacts of development and preventing natural disasters. A good understanding and awareness of the country and region’s vulnerability to various types of disasters such as floods, earthquakes, and landslides are valuable assets. This study aims to examine the impact of spatial planning policies on reducing the negative impacts of development and disasters from a legal perspective, focusing on the analysis of relevant laws and regulations, doctrines, legal principles, and the challenges faced in their implementation. This study uses a legislative and conceptual approach to analyze and describe existing conditions. This approach will also help in understanding the relationship between the application of spatial planning laws and the negative impacts of disasters that occur in various regions. The results of the study indicate that effective spatial planning policies can reduce the negative impacts of development and disasters through appropriate zoning, land use regulations, and the development of disaster-resistant infrastructure. However, challenges such as regulatory compliance, limited resources, and lack of public awareness remain obstacles. This study recommends the need for increased coordination between institutions and public education regarding the importance of spatial planning policies in mitigating the negative impacts of development and disaster threats. Thus, spatial planning policy is something that must be prioritized and optimized in order to create a safer, better-managed, and more sustainable environment for people’s lives.